Психолого-педагогічна діагностика готовності майбутнього вихователя до формування творчої особистості дошкільника - Іщенко Людмила; Орос Ільдіко; Ляховець Олеся; Ishchenko Liudmyla; Oros Ildiko; Liakhovets Olesia; Orosz Ildikó (Південноукраїнський національний педагогічний університет імені К. Д. Ушинського, 2017)
Резюме. Статтю присвячено підготовці майбутніх вихователів до формування творчої особистості дитини дошкільного віку; розв’язується актуальна проблема психолого-педагогічної діагностики готовності студентів вищих навчальних закладів до професійної діяльності з творчими дітьми. Мета дослідження – розкрити результати психолого-педагогічної діагностики готовності майбутнього вихователя до формування творчої особистості дошкільника. Було розроблено діагностувальну методику та такі критерії готовності майбутнього вихователя до формування творчої особистості дошкільника: мотиваційно-ціннісний, когнітивний, практично-діяльнісний, оцінно-рефлексивний. Кожен критерій включає групу якісних показників, які розкривають зміст і дають характеристику досягнень студентів у передбаченому виді діяльності. На основі цього розроблено методичний інструментарій, за яким проведено психолого-педагогічну діагностику сформованості цієї професійної якості у майбутніх вихователів. Це уможливило їх чітку кількісну диференціацію за високим, достатнім, середнім і низьким рівнями готовності із конкретними характеристиками якісних вимірів, що відкриває перспективи для розроблення відповідних ефективних заходів щодо підвищення якості професійної підготовки майбутнього педагога до означеної діяльності.

Abstract. The paper aims to reveal the results of psychological and pedagogical assessment of future tutors’ ability for the formation of creative skills in preschool children. The assessment was carried out according to the following criteria: motivational and value, cognitive, activity, evaluative and reflexive. Each criterion includes a group of qualitative indicators that reveal the content and describe the achievements of students in this type of activity. There have been distinguished high, sufficient, medium and low levels of ability for this activity with specific characteristics of qualitative dimensions, which reveals the prospects for developing appropriate effective measures to improve the quality of professional training of future tutors. The experiment involved 60 students of Pavlo Tychyna Uman State Pedagogical University majoring in Preschool education. According to the results of the performance of a series of diagnostic tasks by the respondents, it has been found that no one of them has a high level of the ability for the formation of a preschoolers’ creative skills. A sufficient level is characteristic of almost a quarter of the students; an average level is peculiar for more than a quarter of the respondents. A low level has been found in about 50% of the students. The results of the study have revealed the main problems of the students associated with the lack of knowledge of scientific and methodological, as well as psycho-pedagogical bases of the specific nature of the organization of the process of preschoolers’ creative skills formation; as well as incompetence of professional skills of carrying out this kind of work. Thus, the carried out research has revealed the need for the development of the efficient technique of increasing the level of training of future tutors in terms of the formation of preschoolers’ creative skills. This technique is going to involve the development of basic psycho-pedagogical disciplines by means of introducing new modules, topics, issues, specialized courses, study guides, trainings focused on the development of preschoolers’ creativity.
Psycho-pedagogical assessment of future tutors’ ability for the formation of preschoolers’ creative skills
http://nbuv.gov.ua/UJRN/NiO_2017_10_12
Keywords: майбутні вихователі; психолого-педагогічна діагностика; методичний інструментарій; критерії; показники; рівні; творча особистість дитина дошкільного віку